2018
DOI: 10.1186/s12882-018-0947-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate binders as a cause of hypothyroidism in dialysis patients: practical indications from a review of the literature

Abstract: BackgroundAlthough fatigue is common in dialysis patients, polypharmacy is seldom listed among its causes. In this report, we describe a dialysis patient who developed severe fatigue due to pharmacological interaction between two commonly prescribed drugs, phosphate binders and levothyroxine.Case PresentationA 65-year old woman, on dialysis for 17 years, complained of fatigue (weight 54 Kg, height 1.55 m, BMI: 23 Kg/m2; malnutrition inflammation index: 10; Charlson index 9). She had been treated with lithium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Literature studies are suggesting that patients with chronic kidney disease on renal replacement therapy, especially patients with thyroid disorders on levothyroxine replacement therapy can have a higher rate of hypothyroidism caused by phosphate binders. Phosphate binders can impair levothyroxine absorption leading to hypothyroidism [52]. However, we did not study this aspect in our study; as only 14 patients were on levothyroxine replacement therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Literature studies are suggesting that patients with chronic kidney disease on renal replacement therapy, especially patients with thyroid disorders on levothyroxine replacement therapy can have a higher rate of hypothyroidism caused by phosphate binders. Phosphate binders can impair levothyroxine absorption leading to hypothyroidism [52]. However, we did not study this aspect in our study; as only 14 patients were on levothyroxine replacement therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Oral activated charcoal could be a safe, effective, and low-cost therapy for patients with uremic pruritus but also for hyperphosphatemia, especially when other treatments are not available. However, non-selective absorption can impede correct bioavailability of several drugs as well as the absorption of some nutrients; interference with the many drugs often prescribed to dialysis patients has not been studied, a problem in common with several widely used, albeit less selective binders [47,48] Oral Charcoal Therapy: AST-120.…”
Section: Oral Charcoal Therapy: Activated Charcoalmentioning
confidence: 99%
“…Clinical studies and case reports have shown that sevelamer binds to levothyroxine, ciprofloxacin, mycophenolic acid, tacrolimus, cyclosporine, vitamin D analogues, lipid soluble vitamins like vitamins A, E, and K, folic acid, quetiapine, furosemide, and levetiracetam. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 For polystyrene sulfonate, binding interactions have been described with lithium, quetiapine, and levothyroxine. 21 , 22 , 23 CKD patients often use many different drugs (average of eight drugs a day), and the prevalence of potential drug–drug interactions in CKD patients is high (75%–91%).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies and case reports have shown that sevelamer binds to levothyroxine, ciprofloxacin, mycophenolic acid, tacrolimus, cyclosporine, vitamin D analogues, lipid soluble vitamins like vitamins A, E, and K, folic acid, quetiapine, furosemide, and levetiracetam 6‐21 . For polystyrene sulfonate, binding interactions have been described with lithium, quetiapine, and levothyroxine 21‐23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation